PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pramitha, Noviana rNoviana (EKONOMIA, 2019)
ABSTRACTRunning a business in the field of transportation is very risky to experience bankruptcy, therefore it's very necessary to have an analytical tool that can produce 95% accurate and reliable results such as the Altman Z-Score, in order to easily predict the level of bankruptcy in a company. This research examines transportation sector companies by taking 9 samples from the Transportation Sector company itself.This study aims to find out: the bankruptcy of PT Pelayaran Bina Raya Tbk, PT Blue Bird Tbk, PT Indonesia Transport & Infrastructure Tbk, PT Tanah Laut Tbk, PT Lugindo Samudramakmur Tbk, PT Rig Tenders Indonesia, PT Samudera Indonesia Tbk, PT Express Transido Utama Tbk, PT Wintermar Offshore Marine Tbk, in the Transportation Sector listed on the Indonesia Stock Exchange in the 2016-2017 period.The analytical tool that been used is the Altman Z-Score with formulation Z=0,717X1 + 0,847X2 +3,07X3+0,420X4+0,998X5, and the formula X1 = Working Capital / Total Assets, X2 = Retained earnings / total assets, X3 = Earning Before Intrest and Taxes / total assets, X4 = Book value of total equity / total liabilities, and finally, X5 = Sales / Total assets.The results of the study conclude, that companies in the Transportation Sector are as follows:PT Pelayaran Bina Raya Tbk is declared bankrupt in 2016-2017, PT Blue Bird Tbk is declared bankrupt in 2016-2017, PT Indonesia Transport & Infrastructure Tbk is declared bankcrupt in 2016-2017, PT Tanah Laut Tbk is declared bankcrupt in 2016-2017, PT Lugindo Samudramakmur Tbk is declared bankcrupt in 2016-2017, PT Rig Tenders Indonesia Tbk is declared bankcrupt in 2016-2017, PT Samudera Indonesia Tbk is declared bankcrupt in 2016-2017, PT Express Transido Utama Tbk declared bankcrupt in 2016-2017, PT Wintermar Offshore Marine Tbk declared bankcrupt in 2016-2017.